(untitled) (Revista científica Olimpia, 2024)
The use of therapeutic physical exercise in the treatment and integral rehabilitation of the burned patient is a resource of outstanding value to get the capacity of movement back as part of the health care of this entity. The present study aims at identifying the influence of a system of physical exercises in the improvement of the strength of muscles affected by hypodermic B burns in the shoulder girdle. This proposal is determined from the study of a sample of 10 people with hypodermic B burns in the shoulder girdle, 6 women and 4 men, with an average age of 39.4 years (23 minimum and 59 maximum), the data collected in the medical records and the results of the initial and final explorations of the osteomyoarticular system were analyzed. The DeLorme-Watkins Method was applied with the intention of determining the evolution of muscle strength. At the end of the intervention, higher results were recorded in each of the elements subjected to evaluation. The system of therapeutic exercises created supports shorter recovery times of the burned patient’s strength.